Kongens Stol i Domus Anatomica Hafniensis - Bruun, Niels W. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
The scientifically-minded King Frederik III often witnessed Thomas Bartholin’s anatomical demonstrations in the anatomy theatre at the University of Copenhagen. On these occasions the monarch, together with his courtiers, occupied what is called a conclave superius, which has been translated as ‘a private apartment on the first floor’. However, the accuracy of such an interpretation may be questioned, particularly because another source describes it as Kongens stol, ‘the king’s chair’. One must therefore inspect the meaning of this stol, which clearly corresponds to the Latin conclave. It consequently appears that stol here signifies a box, which is located aloft, that is, raised above the rest of the seats in the auditorium. Moreover, the king’s box was enclosed, inasmuch as it was provided with a lattice, so that the king and his attendants could survey the anatomical demonstrations unobserved.